Design of the U-slotted oval-shaped phase gradient metasurface and antenna for 5G wireless communication - Devendra Soni; Dinesh Yadav; Manish Tiwari (Results in Engineering, 2025)
The rapid advancement of wireless communication, particularly with the deployment of 5 G networks, necessitates the development of high-performance antennas capable of supporting high data rates, low latency, and efficient spectrum utilization. Phase Gradient Metasurfaces (PGMs) have emerged as a promising technology to enhance antenna performance by improving impedance matching, gain, and bandwidth. In this work, a U-slotted oval-shaped PGM-integrated antenna is proposed for 5 G wireless communication applications. The antenna is designed using an RT/Duroid 5880 substrate with a dielectric constant (εr) of 2.2, a loss tangent (tan δ) of 0.009, and a thickness of 1.6 mm. The PGM, consisting of 49-unit cells arranged in a 7 × 7 grid, covers an area of 42 mm × 42 mm. The antenna's reflection coefficient (S11) without PGM is -27.5 dB at 27.3 GHz, with a bandwidth of 1.74 GHz. With the integration of PGM, the reflection coefficient improves significantly to -70.14 dB at 27.91 GHz, while the bandwidth expands to 4.5 GHz. The antenna gain is enhanced from 7.5 dB without PGM to 12 dB with PGM, demonstrating substantial improvements in radiation performance. These key findings highlight the potential of the proposed PGM-based antenna for 5 G wireless communication applications. The presented antenna design, incorporating a U-slotted oval-shaped PGM, demonstrates improved impedance matching, enhanced gain, and broader bandwidth, making it highly suitable for 5 G wireless communication.